HUBUNGAN PERSEPSI KEBERMANFAATAN DAN KEMUDAHAN DENGAN MINAT PENGGUNA APLIKASI JKN MOBILE DI WILAYAH KERJA UPTD PUSKESMAS SUKAMERINDU KOTA BENGKULU - Viona Prazela; Deltari Novitasari; NH. Noeraini (LPPM STIKES BHAKTI HUSADA BENGKULU, 2025)
Background: The development of digital technology in the health sector has led to the creation of the JKN Mobile application, which aims to make it easier for the public to access National Health Insurance services. However, the usage rate of this application is still low, especially in the working area of the Sukamerindu Community Health Center in Bengkulu City. The research question in this study is the low interest of the public in using the JKN Mobile application. This study aims to determine the relationship between perceived usefulness and perceived ease of use with interest in using the JKN Mobile application. This study uses a quantitative approach with a cross-sectional design. A sample of 48 respondents was obtained using total sampling technique. Data were collected through questionnaires and analyzed using the chi-square test. The results showed that 56.3% of respondents had a high perception of usefulness, 62.5% had a high perception of ease of use, and 66.7% of respondents had a high interest in using the JKN Mobile app. Bivariate analysis showed a significant relationship between perceived usefulness (p=0.020) and perceived ease of use (p=0.005) with interest in using the application. In conclusion, the higher the perceived usefulness and ease of use, the greater the public's interest in using the JKN Mobile application. The researchers suggest that Puskesmas and BPJS Kesehatan increase socialization and education regarding the benefits and how to use the JKN Mobile application to expand access to digital health services, especially for people who are less tech-savvy. Keywords: JKN Mobile, perceived usefulness, perceived ease of use, user interest.